Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fgene.2019.00188
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functional Non-coding Variant in the GABAA Receptor α2 Subunit of the C57BL/6J Mouse Reference Genome: Major Implications for Neuroscience Research

Abstract: GABA type-A (GABA-A) receptors containing the α2 subunit (GABRA2) are expressed in most brain regions and are critical in modulating inhibitory synaptic function. Genetic variation at the GABRA2 locus has been implicated in epilepsy, affective and psychiatric disorders, alcoholism and drug abuse. Gabra2 expression varies as a function of genotype and is modulated by sequence variants in several brain structures and populations, including F2 crosses originating from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
113
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(123 citation statements)
references
References 63 publications
8
113
1
Order By: Relevance
“…There were 23 genomic features that matched the SDP and thus could explain the gene expression difference. The gene expression was consistent with previous findings that C57BL/6J mice have reduced Gabra2 expression levels (40); in that prior study, an intronic indel adjacent to a splice acceptor site was identified at Chr5:71,014,638. Repairing that SNP restored normal expression (40), demonstrating causality.…”
Section: Gabra2supporting
confidence: 91%
“…There were 23 genomic features that matched the SDP and thus could explain the gene expression difference. The gene expression was consistent with previous findings that C57BL/6J mice have reduced Gabra2 expression levels (40); in that prior study, an intronic indel adjacent to a splice acceptor site was identified at Chr5:71,014,638. Repairing that SNP restored normal expression (40), demonstrating causality.…”
Section: Gabra2supporting
confidence: 91%
“…The same phenomenon is true of spontaneous mutations that occurred in the 1980s in the C57BL/6J maternal parent that led to the deletion of Nnt exons and a striking reduction in Gabra2 expression in brain 68,72,73 .…”
Section: Kinship Relations and Genetic Driftmentioning
confidence: 80%
“…detected a surprisingly large number of new variants (n = 47 out of about 13,000 SNPs) in the set of strains generated by Taylor in the early 1990s (BXD33 though BXD42), and a small number (n = 5) of even more recent mutations in BXDs generated in the late 1990s at UTHSC. While the majority of mutations are neutral or non-functional, we already know that a handful produce interesting differences in gene expression and higher order phenotypes among different phases of the BXD family68,69 .Analysis of expression data from different epochs highlights ~50 genes modulated bystrong cis-acting expression QTLs only in newer strains. For example, introduction of a premature stop codon in glycoprotein nmb (Gpnmb) and deletion of the last coding exon in killer cell lectin like receptor D1 (Klrd1; CD94) occurred spontaneously in the DBA/2J…”
mentioning
confidence: 99%
“…An indel, rs225241970 located at 71,031,384 bp, was recently identified as a de novo deletion in B6J that significantly reduced gene expression 38 . When repaired using CRISPR-Cas9 editing, it fully restored expression of Gabra2 in B6J mice 38 . This finding is consistent with our observation on Gabra2 expression and sequence variation.…”
Section: The Most Likely Cause Of Gene Expression Variation In Gabra2mentioning
confidence: 99%